ANALISIS MINAT DAN PERILAKU PENGGUNAAN APLIKASI SHAREIT DENGAN PENDEKATAN UNIFIED THEORY OF ACCEPTANCE AND USE OF TECHNOLOGY - Qona'ah El Hasan; Budi Permana (Jurnal Sistem Informasi dan Informatika (Simika), 2021)
Technology acceptance is important for identifying elements that influence the user, so it is easy to use apps. The evaluation of technology reception will help to improve the system better in the future and indicate whether the system succeeded or not, so the users will keep using the apps. SHAREit is a program that can be downloaded on the Android Smartphone platform and on personal computers. It is able to transfer documents, pictures, music, and videos rapidly. Even so, the applications are faster than Bluetooth and Wifi. Then, Indonesia is the biggest second market for SHAREit in the world. The research is proposed to detect how the user accepts SHAREit in Kuningan Regency by using the Unified Theory of Acceptance and Use of Technology Method. It has been modified. The instrument of research is a questionnaire then distributed to user communities of SHAREit in Kuningan Regency by using Incidental Sampling, instrument testing and data processing Structural Equation Modelling by AMOS apps. Furthermore, the hypothesis is arranged through moderator variables; age, gender, and experience. The result of research indicates that there are three factors possessing positive influence on Behavioral Intention of usage SHAREit, such as Performance Expectancy, Social Influence, and Facilitating Conditions. A factor influencing use of behavioral is behavioral intention. Whereas, Personal Innovativeness in the Domain of Information Technology and Effort Expectancy do not influence the Behavioral Intention of SHAREit Apps in Kuningan Regency.